Synthesis and Characterization of Glutaraldehyde-Crosslinked Chitosan Membrane with Lithium Perchlorate for Lithium Battery Application - Y E Laoh Tambuwun, Daniel
L1thiwn-ion secondaf) battery has some \'veaknesses especially for safet) reason due to the usc of organic electroly1e liquid. In order to O\ercome thiS problem, solid polymer electrolyte membrane is used as a safer substitute. Chitosan is a natural polymer that abundantly fotmd and has good ionic conducti\ ity due to the presence of hydroxyl and amine !:,'TOUps in its structw•e. Chitosan structw•e has been modified v. ith glutaraldehyde as a cross linker and lithiwn perchlorate as a dopant. The yield of isolated chitosan obtained ,... as 1 7.50°o and the deacctylation dee,rree of66.55°o. The a\erage molecular mass ofchitosan as measured b'iscometer is 3.89 10g mot•' . Crosslinked structw•e of chitosan has been fanned. ,..,hich ,.,.as confinned bfTIR analysis in the presence of \ibrauons of the imine group at the wa,enw11ber of 1655 cnY1 and the decreasing \alue of the degree ofs,,eiJing. Thennal stability and the degree of crystallinity of the membrane decrease after the chitosan is modtfied both after the addition of glutaraldehyde and lithium salt . lncreasmg the amatmt of glutaraldehyde to 10° o ( ''" '") m the membrane can increase ionic conducti'il) w1t1l a cet1ain 'alue then decreases again The ionic conducti,ity of the membrane increases ''ith the increase in the amatmt ofLiCI04 in the membrane. The best ionic conducti,ity \alue of membranes in the amount of 5 327 I 0-1 S cnr 1 v. as obtained in the composition of 15°o l iCI04 and I0°o glutaraldehyde. In general, modified chitosan membranes ha\e lower mechanical strength than pure chitosan membranes, but the mechanical strene,rth of the membranes can be increased by the presence of certain amOtmts of glutaraldehyde and LiC104. and a maximwn \alue of tensile strength was obsened in the composition of l5°o L1CI04 and 7°o glutaraldeh de.